Use of BI-Systems for Ensuring Information and Analytical Activity of Public Authorities - Vladimir Nikolaevich Naumov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
This article is devoted to the problems of information - analytical ensuring administrative activity on the basis of use of modern infocommunication technologies. It is told about experience of implementation of programs of professional development for the staff of Administration of the Government of St. Petersburg. The review of BI-of systems is carried out, examples of use of such systems in various branches are given. Need of use of BI -of systems for ensuring information and analytical activity of public authorities is proved. It is offered the new paradigm of tutoring in infocommunication technologies in the highest educational institutions, that train experts of the public and municipal administration.